Projetos de letramento na educação de jovens e adultos: o ensino da escrita em uma perspectiva emancipatória - Santos, Ivoneide Bezerra de Araujo (2012)
This ethnographical research-action is included in the Applied Linguistics area and its study object is related to literacy projects (KLEIMAN, 2000), since they bring a new sense to the literacy practices in school and emphasizes the agentive writing character and the role of the discursive genres in the formation of literacy agents who aim at the action and the social change. Considering the emancipatory potential that these didactic organizations have in the civic literacy of those who live in social risk and vulnerability situations our aim in this investigation is: to reflect about the role of the redefinition of the literacy school practices and investigate how the action of teachers and students as literacy agents occur. The specific aims are: to promote literacy events which encourage the writing practice for the action and social change; to comprehend how the identity construction of the literacy student-agent occurs by the reflection of its agency process in the literacy projects; to identify teaching strategies and procedures which enable the development of emancipatory language practices; to investigate the axiological values constructed by the learners in and about the writing work in literacy projects. Our discussion is based on the language conception supported by Bakhtin (BAKHTIN/VOLOSHINOV, 2000; BAKHTIN, 1990, 2003); in literacy studies (KLEIMAN, 1995; BAYNHAM, 1995; BARTON; HAMILTON; IVANIC, 2000, LAZERE, 2005); on critical studies which defend the idea that the texts are ideological instruments able to give power to the individuals (MCLAREN, 1988, 1991, 1997, 1999, 2000, 2001; FREIRE, 1971, 1978, 1979, 1982, 1992, 1996, 2001a, 2001b, 2009; GIROUX, 1983, 1986, 1990, 1992, 1997, 1999, 2003; APPLE, 1989); on the social genre approach inspired by the New Rhetoric (BAZERMAN, 2005, 2006, 2007; MILLER, 1984, 2009). The data were generated between 2006 and 2010 in the Youth and Adult Education (YAE), in public schools in Natal-RN. The research permitted us to deduce, firstly, that the redefinition of the work with discursive genres provide the learner to read and write to act discursively in the social world, earning, thus, empowerment, autonomy and emancipation; secondly, that involving the students in literacy projects goes beyond didactic competence related to specificities and content domain. It is necessary that the teacher is certain about to whom, what, why and how to teach and that he/she gets a reflexive posture, becoming a learner as well; thirdly, that through the literacy practices which were developed, the collaborators of the research have constructed a more conscious and a more critical view in relation to the language and to the world where they live through the social-political writing and they have improved as interventive and politicized citizens